Mapping the ligand-binding region of Borrelia hermsii fibronectin-binding protein - Brenner, Christiane; Glosse, Katharina; Habicht, Jüri; Simon, Markus M.; Wallich, Reinhard (PLOS ONE, 2013)
Many pathogenic microorganisms express fibronectin-binding molecules that facilitate their adherence to the extracellular matrix and/or entry into mammalian cells. We have previously described a Borrelia recurrentis gene, cihC that encodes a 40-kDa surface receptor for both, fibronectin and the complement inhibitors C4bp and C1-Inh. We now provide evidence for the expression of a group of highly homologues surface proteins, termed FbpA, in three B. hermsii isolates and two tick-borne relapsing fever spirochetes, B. parkeri and B. turicatae. When expressed in Escherichia coli or B. burgdorferi, four out of five proteins were shown to selectively bind fibronectin, whereas none of five proteins were able to bind the human complement regulators, C4bp and C1-Inh. By applying deletion mutants of the B. hermsii fibronectin-binding proteins a putative high-affinity binding site for fibronectin was mapped to its central region. In addition, the fibronectin-binding proteins of B. hermsii were found to share sequence homology with BBK32 of the Lyme disease spirochete B. burgdorferi with similar function suggesting its involvement in persistence and/or virulence of relapsing fever spirochetes.